Pengaruh Kepemimpinan, Beban Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan di Kantor Pusat PT. Manggala Gita Karya - Adeltje Tomahua; Hendy Tannady (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Almost in every company always trying to improve the performance of its human resources in order to survive and develop this also applies at PT Manggala Gita Karya This study aims to determine the influence of Leadership, Workload and Organizational Culture on employee performance at the head office of PT. Mangala Gita Karya. The distribution of the questionnaire was 63 respondents using google form. This study uses a quantitative method with multiple regression analysis method and uses the SPSS25 program. The results showed that Leadership and Workload had a negative and insignificant effect, on the contrary, Organizational Culture had a positive and significant effect on employee performance. The findings of this study can be used as a reference for PT. Manggala Gita Karya to evaluate the performance of its employees.